The Anthropocene and the Technogene: stratigraphic temporal implications of the geological action of humankind - Oliveira, Antonio Manoel dos Santos; Peloggia, Alex Ubiratan Goossens (Quaternary and Environmental Geosciences, 2014)
During the last years some original ideas concerning the geochronologic implications of human geological activities have been proposed, such as the Technogene and Anthropocene concepts as new geological periods. The essential aspects of the issue are the magnitude and frequency of these activities, the extent and significance of their correlative geological records and, of course, the nature of the stratigraphic time-related classification itself. In this paper we propose an alternative solution, which takes into account diachronic units (namely geotechnogenic events and phases) as appropriated for classifying the products of geological human action during the Quaternary